GERAKAN PEMBEBASAN ISLAM PATANI DI THAILAND SELATAN: Studi atas Patani United Liberation Organization (PULO), 1968-1993 - Jamaludin Helen Sabira Adib (Fakultas Adab dan Humaniora UIN Raden Fatah, 2016)
Assimilation policy of the Thai government that wants to establish the Kingdom of Siam Kingdom have led to a conflict. The government's policy intends to mengsimilasi Patani Malay-Thai-Buddha in terms of religion and culture have led to a resistance and the movement of the Patani Malay-Muslim majority. Cultural and religious differences between Thai Buddhists and Malay-Muslim Patani it is one factor that drives the desire-Patani Malays of Patani Raya founded by an autonomous region. However, this desire raises the ongoing conflict between the two ethnic groups. That's why groups were emerging resistance among Patani Malay Muslim community against the Thai government that is culturally synonymous with Buddhism. One insurgent was Patani United Liberation Organization (PULO), established in 1968. Keywords: -PULO, -Pattani-Malay, -politics conflict